Word Formation as a Means to Realize the Creative Peculiarities of Language - HAYRAPETYAN, ASHOT (Bulletin of Yerevan University B: Philology, 2021)
Language is the greatest cultural creation of human society and is realized as a primary tool for communication. Each speaker is a bearer of socially and objectively existing common language as a system of inherent qualities. The functioning of the mentioned system in communication is a specific creative process itself. This creativity is most obviously demonstrated in word formation. Academician Ed. Aghayan singled out the main tools of word formation in Armenian. According to our approach the methods of word formation in Armenian are: linear/morphemic/ word formation, which for centuries has been a dominant tool in enriching and developing the Armenian vocabulary, and nonlinear/inner/ word formation which is the result of a specific modification of meanings, morphological features and syntactic applications of a word. Both methods have been productive throughout the historical development of the vocabulary of Armenian language, especially in its present phase. Words created through the application of the mentioned methods differ from each other in expression and content.
Keywords: word creativity, parts of speech transmission, word formation patterns, word creativity, metonymy, grammatical meaning, linear word formation, nonlinear word formation, conversion